2017
DOI: 10.1136/bmjopen-2017-016244
|View full text |Cite
|
Sign up to set email alerts
|

The 2015 Middle Childhood Survey (MCS) of mental health and well-being at age 11 years in an Australian population cohort

Abstract: PurposeThe Middle Childhood Survey (MCS) was designed as a computerised self-report assessment of children’s mental health and well-being at approximately 11 years of age, conducted with a population cohort of 87 026 children being studied longitudinally within the New South Wales (NSW) Child Development Study.ParticipantsSchool Principals provided written consent for teachers to administer the MCS in class to year 6 students at 829 NSW schools (35.0% of eligible schools). Parent or child opt-outs from partici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
47
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 41 publications
(50 citation statements)
references
References 33 publications
3
47
0
Order By: Relevance
“…Of 32,389 children enrolled at these schools, 27,808 (85.9%) participated; opt‐outs were received from 816 children and 573 parents, and 3,192 children did not participate for other reasons (e.g., absence from school or technical failure). On a range of socio‐demographic indicators, these participating schools and children were determined to be representative of the population of NSW schools and children of this age (see Laurens et al ., ). Ethical approval for the MCS was obtained from the University of NSW Human Research Ethics Committee (reference HC14307) and the NSW Department of Education's State Education Research Applications Process (reference 2015082).…”
Section: Methodsmentioning
confidence: 97%
See 2 more Smart Citations
“…Of 32,389 children enrolled at these schools, 27,808 (85.9%) participated; opt‐outs were received from 816 children and 573 parents, and 3,192 children did not participate for other reasons (e.g., absence from school or technical failure). On a range of socio‐demographic indicators, these participating schools and children were determined to be representative of the population of NSW schools and children of this age (see Laurens et al ., ). Ethical approval for the MCS was obtained from the University of NSW Human Research Ethics Committee (reference HC14307) and the NSW Department of Education's State Education Research Applications Process (reference 2015082).…”
Section: Methodsmentioning
confidence: 97%
“…Children rated the items on a 3‐point response scale: Not True (scored 1 for LCA), Somewhat True (2), and Certainly True (3). The nine items have excellent ordinal alpha reliability ( α = .90; Laurens et al ., ). Criterion validity of self‐reported PLEs assessed by questionnaire in 11–13‐year‐old children relative to symptoms validated by clinical interview has been established (Kelleher, Harley, Murtagh, & Cannon, ), with greatest predictive power for auditory and visual hallucinations, and paranoid ideas (these items accurately predict clinician‐rated symptoms at interview for at least four in five children).…”
Section: Methodsmentioning
confidence: 97%
See 1 more Smart Citation
“…It also aims to identify new opportunities for detecting and mitigating early vulnerability for ill-health and other adverse outcomes. In 2015, the investigator team administered online a self-report survey of mental health and wellbeing to a subsample of children in the NSW-CDS cohort (the Middle Childhood Survey; MCS), via 829 primary (elementary) schools in NSW (Laurens et al, 2017). MCS data were obtained from 27,792 children aged approximately 11 years of age during their final year of primary schooling (Year 6 in NSW).…”
Section: Research Contextmentioning
confidence: 99%
“…It offers the opportunity to address the question: Does whole-school mental health promotion make a difference to the social, emotional, behavioural and educational outcomes of children? Such work is envisaged to occur within the NSW-CDS cohort (Carr et al, 2016; in press), via linkage to the self-reported Middle Childhood Survey mental health and wellbeing outcomes gathered from children at approximately 11 years of age, in their final year of primary schooling (Laurens et al, 2017), as well as multi-agency administrative records (Carr et al, 2016;Green et al, in press). Accordingly, examining the relationship between the SSPESH and student social emotional health over time is beyond the scope of the present paper, but will be explored in subsequent manuscripts from the study.…”
Section: Limitations and Future Researchmentioning
confidence: 99%